Autoantibody profile in individuals with chronic hepatitis C - Maíra Luciana Marconcini; Leonardo Fayad; Maria Beatriz Cacese Shiozawa; Esther Buzaglo Dantas-Correa; Leonardo de Lucca Schiavon; Janaína Luz Narciso-Schiavon (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
Introduction Autoantibodies are often produced during infection with chronic hepatitis C virus (HCV), but it remains controversial whether they influence the biochemical profile and histological features of this disease. Therefore, this current study sought to describe these autoantibodies and evaluate their impact on the clinical and histological presentation of hepatitis C. Methods This cross-sectional analytical study assessed patients with HCV (RNA+) from October 2011 to July 2012. Results This study included 66 patients, with a mean age of 53.2±10.5 years. Of these patients, 60.6% were male, and 54.3% presented with genotype 1. Non-organ-specific autoantibodies (NOSA) were detected in 24% of the patients; of these, 7.6% were anti-mitochondrial antibodies (AMA+), 26.7% were anti-smooth muscle antibodies (SMA+) and 6.8% were liver kidney microsomal type 1 antibodies (LKM1+). With respect to the thyroid autoantibodies, 7.4% were anti-peroxidase (ATPO+) antibodies, and none were anti-thyroglobulin (ATG+) antibodies. Regarding celiac disease autoantibodies, 5.8% were endomysial antibodies (EMA+), and no transglutaminase (TTG+) antibodies were detected. Cryoglobulins were found in 2.1% of patients. When NOSA+ individuals were compared to patients without the presence of NOSAs, they exhibited higher median alkaline phosphatase (0.7 vs. 0.6 xULN; p=0.041), lower median platelet counts (141,500.0 vs. 180,500.0/mm 3 ; p=0.036), lower mean prothrombin activity (72.6±11.5% vs. 82.2±16.0%; p=0.012) and an increased prevalence of significant fibrosis (E≥2) (45.5% vs. 18.2%; p=0.012). There was also a tendency for a greater proportion of NOSA+ cases to have marked periportal activity (APP≥3) (44.5% vs. 15.6%; p=0.087). Conclusions In addition to the high prevalence of autoantibodies associated with HCV infection, it was observed that NOSA positivity was associated with a more severe histological and biochemical profile of hepatitis C infection.